Trauma and Maternal Caregivers as Risks for Executive Function Deficits Among Youth Who Have Sexually Harmed. (February 2022) - Brown, Adam; Yoder, Jamie; Fushi, Kristina
Despite robust research linking trauma events to the commission of sexual harm by youth, the majority of victims do not become victimizers, imploring us to study potential interceding influences. Some research indicates that intermediary factors like attachment characteristics, trauma symptomatology, and executive functioning may be critical in understanding sexual harm committed by youth. This study explored relationships between trauma events, trauma symptoms, and attachment characteristics, and their relationship to executive functioning in a sample of 196 youth who committed sexual harm. Results revealed bivariate associations between trauma events, symptomatology, and maternal attachment characteristics. Structural equation modeling revealed numerous direct and indirect effects on the path to deficits in executive functioning, and that sexual abuse, above and beyond other forms of traumatic events, contributed to executive functioning deficits via trauma symptoms. The results are contextualized and implications are discussed.